Pattern changes in determinants of Chinese emissions. (27th June 2017) - Mi, Zhifu; Meng, Jing; Guan, Dabo; Shan, Yuli; Liu, Zhu; Wang, Yutao; Feng, Kuishuang; Wei, Yi-Ming
Abstract: The Chinese economy has been recovering slowly from the global financial crisis, but it cannot achieve the same rapid development of the pre-recession period. Instead, the country has entered a new phase of economic development—a 'new normal'. We use a structural decomposition analysis and environmental input–output analysis to estimate the determinants of China's carbon emission changes during 2005–2012. China's imports are linked to a global multi-regional input–output model based on the Global Trade and Analysis Project database to calculate the embodied CO2 emissions in imports. We find that the global financial crisis has affected the drivers of China's carbon emission growth. From 2007 to 2010, the CO2 emissions induced by China's exports dropped, whereas emissions induced by capital formation grew rapidly. In the 'new normal', the strongest factors that offset CO2 emissions have shifted from efficiency gains to structural upgrading. Efficiency was the strongest factor offsetting China's CO2 emissions before 2010 but drove a 1.4% increase in emissions in the period 2010–2012. By contrast, production structure and consumption patterns caused a 2.6% and 1.3% decrease, respectively, in China's carbon emissions from 2010 to 2012. In addition, China tends to shift gradually from an investment to a consumption-driven economy. The proportion of CO2 emissions induced by consumption had a declining trend before 2010 but grew from 28.6%–29.1% during 2010–2012.